Effects of M&A Announcement on Shareholders Wealth: New Evidence from The US Market During Recession - Wadhwani, Rahul (2012)
This study examines the shareholder returns for US publically traded firms that have been involved in M&A activity in the short term (5 day event window) during the global financial crisis. On a general scale the study documents that bidders acquiring public targets obtain a negative abnormal return of -3.45%. Further the study scrutinizes the distinction in the announcement returns by isolating the sample on the basis of different deal characteristics like acquirer size, relative size of target, payment methods, diversification and targets tobin’s Q Ratio. The results for these characteristics are in line with the hypothesis developed from past literature and empirical researches. The results of the univariate tests suggest that larger acquirer size, larger relative size to target, focused acquisitions and target firms with tobin Q Ratio more than 1 are negatively related to the abnormal returns experienced by shareholders. A striking pattern that is observed is that cash financed transactions outperform the stock financed transactions consistently even after considering deal characteristics. Finally suggestions are made that can help formulate stronger conclusive results.